A-063 Viewer Engagement Modulates Activation of Social Brain Systems: Evidence from a Natural Viewing fMRI Paradigm. (28th August 2020) - J, Pincus; S, Koirala; L, Li; A, Klin; W, Jones; S, Shultz
Abstract: Objective: Engagement is critical for social learning—information that does not engage cognition, even when looked at, will go unprocessed and unlearned. Consequently, atypical engagement can contribute to social disability. Despite its importance, the neural mechanisms underlying engagement remain unknown, largely because no studies have successfully quantified the individualized ways that viewers engage with the world. This study uses patterns of eye-blinking—a novel measure of engagement (Shultz, Klin, Jones, 2011)—to examine how a viewer's own engagement with social stimuli (e.g. faces) modulates activation of social brain systems. Method: Simultaneous functional MRI and eye-tracking data were collected while children (n = 12, ages 8–12) watched naturalistic social videos of children interacting. Eye-fixation and blink patterns were used to identify moments when viewers looked at a face and were 'highly engaged' or 'less engaged' with those faces. Whole-brain analyses compared brain activation in response to each condition of interest ('highly engaging faces', 'less engaging faces'). Results: Whole-brain analyses (z = 2.3, cluster corrected at p < .05) reveal increased activation in bilateral occipital cortex, left middle temporal gyrus, bilateral posterior cingulate, left orbitofrontal cortex and inferior frontal gyrus, right angular gyrus, and right fusiform gyrus, when viewing faces perceived as 'highly engaging' versus 'less engaging'. Conclusion: Findings suggest that even when viewing the same stimulus category (e.g. faces), one's own engagement with the stimulus modulates brain activation, even in canonical face processing areas like the fusiform gyrus. Insights into the neural mechanisms of engagement can inform future understanding of social disability and interventions for social learning.